Phosphorylations of Serines 21/9 in Glycogen Synthase Kinase 3α/β Are Not Required for Cell Lineage Commitment or WNT Signaling in the Normal Mouse Intestine. - Fiona Hey; Susan Giblett; Stephanie Forrest; Chelsea Herbert; Catrin Pritchard (PLoS ONE)
The WNT signalling pathway controls many developmental processes and plays a key role in maintenance of intestine renewal and homeostasis. Glycogen Synthase Kinase 3 (GSK3) is an important component of the WNT pathway and is involved in regulating β-catenin stability and expression of WNT target genes. The mechanisms underpinning GSK3 regulation in this context are not completely understood, with some evidence suggesting this occurs through inhibitory N-terminal serine phosphorylation in a similar way to GSK3 inactivation in insulin signaling. To investigate this in a physiologically relevant context, we have analysed the intestinal phenotype of GSK3 knockin mice in which N-terminal serines 21/9 of GSK3α/β have been mutated to non-phosphorylatable alanine residues. We show that these knockin mutations have very little effect on overall intestinal integrity, cell lineage commitment, β-catenin localization or WNT target gene expression although a small increase in apoptosis at villi tips is observed. Our results provide in vivo evidence that GSK3 is regulated through mechanisms independent of N-terminal serine phosphorylation in order for β-catenin to be stabilised.